2021
DOI: 10.3389/fcell.2021.753194
|View full text |Cite
|
Sign up to set email alerts
|

PPARβ/δ Agonist Alleviates Diabetic Osteoporosis via Regulating M1/M2 Macrophage Polarization

Abstract: Diabetic osteoporosis is a common complication in diabetic patients, leading to increased fracture risk and impaired bone healing. As a member of the peroxisome proliferator-activated receptor (PPAR) family, PPARβ/δ agonist is suggested as a therapeutic target for the treatment of metabolic syndrome, and has been reported to positively regulate bone turnover by improving osteogenesis. However, its regulatory role in diabetic osteoporosis has not been reported yet. Here, we explored the therapeutic effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…This is not necessarily a pro-inflammatory action, as COX-2 catalyzes a common step in the synthesis of both pro- and anti-inflammatory eicosanoids 33 . The mediation of PPAR β/δ in this effect of MCFA is in line with prior experiments showing that PPAR β/δ is important for the polarization of macrophages towards the anti-inflammatory M2 phenotype, characterized by reduced activity of the NF-kB pathway 34 .…”
Section: Discussionsupporting
confidence: 88%
“…This is not necessarily a pro-inflammatory action, as COX-2 catalyzes a common step in the synthesis of both pro- and anti-inflammatory eicosanoids 33 . The mediation of PPAR β/δ in this effect of MCFA is in line with prior experiments showing that PPAR β/δ is important for the polarization of macrophages towards the anti-inflammatory M2 phenotype, characterized by reduced activity of the NF-kB pathway 34 .…”
Section: Discussionsupporting
confidence: 88%
“…This is not necessarily a pro-in ammatory action, as COX-2 catalyzes a common step in the synthesis of both pro-and anti-in ammatory eicosanoids (30). The mediation of PPAR b/d in this effect of MCFA is in line with prior experiments showing that PPAR b/d is important for the polarization of macrophages towards the anti-in ammatory M2 phenotype, characterized by reduced activity of the NF-kB pathway (31).…”
Section: Discussionsupporting
confidence: 83%
“…Osteoporosis is a common disease in elderly people, with osteoporosis caused by T2DM considered the most detrimental. 144 Experiments in mice models have revealed that the PPARβ/δ agonist 145 and exendin-4 synergized with vitamin D 146 aid in the improvement of diabetic osteoporosis due to the correction of macrophage dysfunction via facilitating M1/M2 macrophage polarization. Co-culture of osteoclasts (OCs) and neutrophils in the HG environment revealed an increase in apoptotic neutrophils and a loss of efferocytosis of OCs, which could be reversed by an efferocytosis activator such as lipoxin A4 and insulin.…”
Section: Efferocytosis In Pathologies and Therapeutic Opportunities O...mentioning
confidence: 99%